Research, HIV/AIDS, and Turning Waria into a Key Population in Indonesia: An Ethnographic Oral History - Hegarty, Benjamin; Thajib, Teuku Ferdiansyah; Handayani, Amalia Puri; Mallay, Rully; Marischa, Arum (Medical Anthropology, 2024)
The history of HIV/AIDS is often told from the Global North, a viewpoint that is naturalized in policies and programs that privilege biomedical models of treatment and prevention. This article explores how one Indonesian transgender population known as waria became the subject of various forms of research since the 1980s. Research was one way that waria came to be classified as part of the key population of “transgender people.” Drawing on an oral history project conducted in 2021/2022, we show how–while necessarily hierarchical–ethnographic accounts of other HIV/AIDS histories can rethink fundamental global health concepts.
CRIS-Team Scopus Importer:2024-11-29
Keywords: Ethics; HIV/AIDS; Indonesia; key populations; oral history; transgender